Human dorsal-root-ganglion perfusion measured in-vivo by MRI - Godel, Tim; Pham, Mirko; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (NeuroImage, 2016)
PURPOSE: To develop an in-vivo imaging method for the measurement of dorsal-root-ganglia-(DRG) perfusion, to establish its normal values in patients without known peripheral nerve disorders or radicular pain syndromes and to determine the physiological spatial perfusion pattern within the DRG. - METHODS: This prospective study was approved by the institutional ethics committee and written informed consent was obtained from all participants. 46 (24 female, 22 male, mean age 46.0±15.2years) subjects without known peripheral neuropathies or pain syndromes were examined by a 3Tesla MRI scanner (Magnetom VERIO or TRIO, Siemens AG, Erlangen, Germany) with a VIBE (Volume-Interpolated-Breathhold-Examination) dynamic-contrast-enhanced (DCE) T1-w-sequence (TR/TE 3.3/1.11ms; 24 slices; voxel resolution 1.3×1.3×3.0mm(3)) covered the pelvis from the upper plate of the 5th lumbar vertebra to the 2nd sacral vertebra. Transfer-constant (K(trans)) and interstitial-volume-fraction (interstitial-leakage-fraction, Ve) were modeled for the DRG and spinal nerve by applying the Tofts-model. Statistical analyses included pairwise comparisons of L5/S1 DRG vs. spinal nerve. Furthermore, distinct physiological zones within the S1 DRG were compared (cell body rich area (CBRA) vs. nerve fiber rich area (NFRA)). - RESULTS: DRG showed a significantly increased permeability compared to spinal nerve (K(trans) 3.8±1.5 10(-3)/min vs. 1.6±0.9 10(-3)/min, p-value: <0.001) combined with an increased interstitial leakage of contrast agent into the extravascular-extracellular-space (Ve 38.1±19.2% vs. 17.3±9.9%, p-value: <0.001). Parameters showed no statistically significant difference on DRG-level (L5 vs. S1; p-value: 0.62 (K(trans)); 0.17 (Ve)) and -side (left vs. right; p-value: 0.25 (K(trans)); 0.79 (Ve)). Female gender was associated with a significantly increased permeability (K(trans) female 4.3±1.4 10(-3)/min vs. male 3.4±0.9 10(-3)/min, p-value: <0.05) but no statistically significant differences in interstitial leakage (Ve female 40.1±14,1% vs. male 34.5±17.4%, p-value: 0.24). DRG showed distinct spatial distribution patterns of perfusion: K(trans) and Ve were significantly higher in the CBRA than in the NFRA (K(trans) 4.4±1.8 10(-3)/min vs. 1.7±1.2 10(-3)/min, p-value: <0.001 and Ve 40.9±21.3% vs. 15.1±11.7%, p-value: <0.001). - CONCLUSION: Non-invasive and in-vivo measurement of human DRG perfusion by MRI is a feasible technique. DRG show substantially higher permeability and interstitial leakage than spinal nerves. Even distinct physiological perfusion patterns for different microstructural compartments could be observed within the DRG. The technique may become particularly useful for future research on the poorly understood human sensory neuropathies and pain syndromes.
Gesehen am 24.06.2020